The Paradigm of Religious Moderation in Building Moderate Islamic Education: Analysis of the Indonesian Ministry of Religion’s Concept of Religious Moderation - Fahrul Rozi; Mutohharun Jinan; Iyas Ali Nurani (International Journal of Emerging Issues in Islamic Studies, 2025)
The plurality of society in Indonesia allows for the emergence of ethnic, racial, and religious-related social conflicts. Religious moderation is therefore needed as an answer to this multicultural condition. Religious moderation should be made a life choice in Indonesia’s society, nation, and state. Education moderation is the best means to achieve this. This research focuses on the paradigm of religious moderation formulated into the concept of Islamic education moderation initiated by the Ministry of Religious Affairs of the Republic of Indonesia through Hilda Taba’s education theory related to the development of the Islamic education curriculum. This study aims to provide an overview of the paradigm of educational moderation in Islam to develop a moderate Islamic education curriculum in Indonesia. This library research is based on written literature and the method of data collection through documentation techniques using descriptive analysis techniques. Interpretation is carried out in this study as a means of understanding the study object based on the author’s abilities. Religious moderation can be understood as a procedure for attitudes, views, and behavior that seeks to choose a position in the middle, acting fairly and not extreme in religious practice. There are nine values of strengthening religious moderation in Islamic education: tawassut, i'tidal, tasamuh, ash-shura, al-islah, al-qudwah, al-muwathanah, al-'unf, and i'tiraf al-'urf. These moderate values form the foundation that will be internalized in the development of moderate educational curricula and practices